2007
DOI: 10.1080/03602550601152861
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Thermal Ageing Degradation, Dynamic Properties, Cure Systems, and Antioxidants in Natural Rubber Vulcanisates

Abstract: The present work aims to study the relationship among the thermal ageing stability, dynamic properties, cure systems, and antioxidants in natural rubber (NR) vulcanisates. Thermal degradation behavior of NR vulcanisates has been investigated and correlated to the changes in cross-link density, tensile and dynamic mechanical properties. The results obtained show that thermal ageing properties of NR vulcanisates depend strongly on cross-link density, which changes during thermal oxidative ageing or the so-called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 19 publications
2
35
1
Order By: Relevance
“…This is because, as the aging proceeds [29], the molecular weight of the rubber increases and chain molecules are generated, thereby widening the molecular-weight distribution. Thus, the rubber molecules have reduced flexibility [30], which limits the intermolecular slippage and reduces the swelling [31]. In the case of unaged specimens, the initial crosslink density is about 4.5 × 10 −5 mol/cm 3 , and it can be confirmed that the crosslink density increases up to 14.5 × 10 −5 mol/cm 3 as the aging progresses.…”
Section: Swelling-test Resultssupporting
confidence: 52%
“…This is because, as the aging proceeds [29], the molecular weight of the rubber increases and chain molecules are generated, thereby widening the molecular-weight distribution. Thus, the rubber molecules have reduced flexibility [30], which limits the intermolecular slippage and reduces the swelling [31]. In the case of unaged specimens, the initial crosslink density is about 4.5 × 10 −5 mol/cm 3 , and it can be confirmed that the crosslink density increases up to 14.5 × 10 −5 mol/cm 3 as the aging progresses.…”
Section: Swelling-test Resultssupporting
confidence: 52%
“…In the aging process, oxidative crosslinking was slightly greater than degradative chain scission, and the number of crosslinking points between macromolecular networks was increased and the flexibility of molecules was decreased, which limited the intermolecular slip [31,32] and resulted in the slow increase of the crosslinking density of HTPB coating. There existed an exponential function relationship between crosslinking density and aging time, which was also widely used in the analysis of the thermal accelerated aging test [33,34], as shown in Equation (1):…”
Section: Aging Results Of Crosslinking Densitymentioning
confidence: 99%
“…The fitting results are shown in Table 1 and the fitting curve is shown in Figure 3. It can be seen from the fitting results that the correlation coefficient between the fitting results of In the aging process, oxidative crosslinking was slightly greater than degradative chain scission, and the number of crosslinking points between macromolecular networks was increased and the flexibility of molecules was decreased, which limited the intermolecular slip [31,32] and resulted in the slow increase of the crosslinking density of HTPB coating.…”
Section: Aging Results Of Crosslinking Densitymentioning
confidence: 99%
“…Moreover, high‐tensile properties of ICCF are attributable to the improvement in tensile strength and modulus for the fiber composite compared with NR matrix. The increase in M300 of biocomposites due to improvement in crosslinking density and the incorporation of ICCF into the rubber matrix increased the stiffness of the vulcanizates as it represents the material stiffness …”
Section: Resultsmentioning
confidence: 99%